A Bayesian approach to Essential Tremor plus: A preliminary analysis of the TITAN cohort. (October 2022) - Erro, Roberto; Pilotto, Andrea; Magistrelli, Luca; Olivola, Enrica; Nicoletti, Alessandra; Di Fonzo, Alessio; Dallocchio, Carlo; Di Biasio, Francesca; Bologna, Matteo; Tessitore, Alessandro; De Rosa, Anna; Gigante, Angelo Fabio; et al.
Abstract: Background: The construct of Essential Tremor plus (ET-plus) refers to patients who also have rest tremor and/or mild neurologic signs of unknown significance. It is unclear whether soft signs represent confounding factors or are useful in suspecting an alternative condition. Methods: Using a Bayesian approach to ET-plus patients recruited in The ITAlian tremor Network (TITAN), we analyzed the probability that these patients do not have ET. Results: The data of 274 ET-plus patients were extracted from the TITAN database. The majority of patients (240/274; 87.5%) had a single soft sign. The post-test probability of not having ET was different according to the specific soft sign: namely, 0.64 (rest tremor); 0.46 (questionable dystonia); 0.85 (questionable bradykinesia); 0.19 (soft gait impairment); and 0.09 (questionable cognitive issues). In patients with multiple soft signs, the post-test probability of not having ET was higher than 50% for 7 out of 11 combinations, accounting for 44.1% of subjects. Overall, the post-test probability of not having ET was higher than 50% in up to 71.5% of ET-plus patients. Discussion: We have here shown that: 1) the soft signs differently contribute in modulating the probability that a patient does not have ET; and 2) the effect of multiple soft signs are not always addictive. Future studies are needed to collect prevalence figures of soft signs in different neurological disorders as well as in the elderly and to calculate their value in predicting the development of an alternative tremor syndrome. Highlights: Soft signs in Essential Tremor might indicate an alternative diagnosis. The probability of not having Essential Tremor is different according to the specific soft sign. Deep clinical phenotyping in Essential Tremor is required for prognostication.